EVALUATING THE IMPACT OF THE COVID-19 PANDEMIC ON URGENT MEDICAL ACCESS FOR PATIENTS WITH INFLAMMATORY BOWEL DISEASE AT A PRIVATE COMMUNITY GASTROENTEROLOGY PRACTICE. (22nd January 2022) - Kwon, Michelle; Tse, Chung Sang; van Deen, Welmoed; Danielewicz, Michael; Ward, Christopher; Kogan, Lawrence; Saeed, Firrah; Shah, Samir
Abstract: BACKGROUND: Patients with inflammatory bowel disease (IBD) are subject to frequent emergency department (ED) visits. In order to decrease unnecessary ED utilization, we established an urgent care hotline (IBD URGENT) at a private community gastroenterology practice to triage pressing concerns from our patients with IBD. However, at the beginning of the Coronavirus disease 2019 (COVID-19) pandemic in Mar 2020, in-person visits were converted to telehealth visits, which could have adversly impacted patient care. Therefore, we examined the impact of the COVID-19 pandemic on the access and utilization of urgent healthcare by patients with IBD. METHODS: In Jun 2018 we implemented a triage system involving gastroenterologists, nurses, and support staff to enable patients to contact our practice for urgent IBD issues with the goal of providing a plan of action from a provider within 4 hours of the call. Incoming patient calls were flagged with a red exclamation mark and labeled as "IBD URGENT" in our electronic medical record (eClinicalWorks) if they met any of the following criteria: new, severe abdominal pain; new, severe anal pain; fever greater than 101F; refractory emesis; or anything otherwise deemed urgent by the clinic nurses. Patients were then either advised to present to the ED for immediate evaluation, scheduled for same-day/next-day medical appointment +/- urgent labs, or received medical advice such as medication changes. The number (two-sample t-test) and triage (two-sample Z-test) of IBD URGENT calls were compared between pre-COVID (Jun 2018-Feb 2020) and post-COVID (Mar 2020-Sep 2021). RESULTS: A total of 366 IBD URGENT calls were received and 91% had a response from a provider within 4 hours (Figure 1). The average number of IBD URGENT calls received per month were comparable pre- and post-COVID (10 vs 9, p=0.32). From Mar 2020 onwards, 40% of IBD URGENT calls were managed by urgent appointments, 51% medical advice, and only 9% ED visits, which was comparable to pre-COVID (Table 1). CONCLUSION: It is reassuring that the COVID-19 pandemic did not cause any significant changes to the utilization and triage outcomes of the urgent IBD hotline system in our practice. Timely clinical operational changes to meet the needs of patients with the onset of the pandemic has allowed our proportion of ED visits to remain comparable to pre-COVID despite the decrease in in-person visits. As we return to normal operations, we plan to sustain our urgent hotline service by educating new staff and by reminding our patients of the IBD URGENT service. We believe this service improves quality of care for patients with IBD by avoiding unnecessary ED visits that often include overuse of Computer Tomography (CT) scans and prescription of steroids and narcotics—all associated with significant risks and financial costs.